Sex chromosomes and karyotype of the (nearly) mythical creature, the Gila monster, Heloderma suspectum (Squamata: Helodermatidae) - Johnson Pokorná, Martina; Rovatsos, Michail; Kratochvíl, Lukáš (PLoS One, 2014)
A wide variety of sex determination systems exist among squamate reptiles. They can therefore serve as an important model for studies of evolutionary transitions among particular sex determination systems. However, we still have only a limited knowledge of sex determination in certain important lineages of squamates. In this respect, one of the most understudied groups is the family Helodermatidae (Anguimorpha) encompassing the only two venomous species of lizards which are potentially lethal to human beings. We uncovered homomorphic ZZ/ZW sex chromosomes in the Gila monster (Heloderma suspectum) with a highly heterochromatic W chromosome. The sex chromosomes are morphologically similar to the ZZ/ZW sex chromosomes of monitor lizards (Varanidae). If the sex chromosomes of helodermatids and varanids are homologous, female heterogamety may be ancestral for the whole Anguimorpha group. Moreover, we found that the karyotype of the Gila monster consists of 2n = 36 chromosomes (14 larger metacentric chromosomes and 22 acrocentric microchromosomes). 2n = 36 is the widely distributed chromosomal number among squamates. In his pioneering works representing the only previous cytogenetic examination of the family Helodermatidae, Matthey reported the karyotype as 2n = 38 and suggested a different chromosomal morphology for this species. We believe that this was probably erroneously. We also discovered a strong accumulation of telomeric sequences on several pairs of microchromosomes in the Gila monster, which is a trait documented relatively rarely in vertebrates. These new data fill an important gap in our understanding of the sex determination and karyotype evolution of squamates.
Keywords: srovnávací genomová hybridizace; zvířata; mužské pohlaví; Sex Chromosomes; Lizards; hybridizace in situ; DNA Barcoding, Taxonomic; pohlavní chromozomy; počítačové zpracování obrazu; Comparative Genomic Hybridization; Female; Karyotyping; výpočetní biologie; Male; Image Processing, Computer-Assisted; karyotypizace; taxonomické DNA čárové kódování; Animals; mitochondriální DNA; ženské pohlaví; In Situ Hybridization; DNA, Mitochondrial; procesy určující pohlaví; Sex Determination Processes; ještěři; Computational Biology